2020
DOI: 10.1021/acs.analchem.0c00860
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Crystallization Pathways of Polymorphic Pharmaceuticals Revealed in Segmented Flow with Inline Powder X-ray Diffraction

Abstract: Understanding the transitions between polymorphs is essential in the development of strategies for manufacturing and maximizing the efficiency of pharmaceuticals. However, this can be extremely challenging: crystallization can be influenced by subtle changes in environment such as temperature and mixing intensity or even imperfections in the crystallizer walls. Here, we highlight the importance of in situ measurements in understanding crystallization mechanisms, where a segmented flow crystallizer was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…Authors observed the transformation of P­(III) into the P­(I) form in a MeOH slurry. In contrast, the reverse partial transition was indicated for a dry P­(I) sample under ambient conditions . The summary of all experiments studying UBA polymorphs is provided in Table S4.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors observed the transformation of P­(III) into the P­(I) form in a MeOH slurry. In contrast, the reverse partial transition was indicated for a dry P­(I) sample under ambient conditions . The summary of all experiments studying UBA polymorphs is provided in Table S4.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To overcome these limitations, molecular dynamics methods were introduced to the studies of polymorphism. , Recently, metadynamics simulations , were used to analyze the disappearing conformational polymorph of succinic acid . In our studies, Born–Oppenheimer molecular dynamics (BOMD) calculations were used to investigate the self-assembly and stability of three urea–barbituric acid (UBA) polymorphs. , The BOMD results were compared with the analysis of H-bond propensities, coordination scores (CS), and the previous experimental data in the context of known thermodynamic stability rules. , Despite numerous experimental and theoretical trials, the “metastability” of the polar UBA polymorph is still unclear. To our knowledge, UBA form (II) can be called one of the first known examples of disappearing co-crystal polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…We additionally show that nucleating agents that promote crystallization in the "bulk" of the droplet further reduce scaling and are an excellent system for studying with DMC-XRD. The seeding of crystallising solutions with a target material is of great importance in the pharmaceutical and chemical industries, [36][37][38][39] and has recently been recognized as a way to reduce the clogging of flow crystallisers. 40 The results presented here demonstrate that foreign material which promotes heterogeneous nucleation in solution can also reduce scale build-up on reactor surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9 However, experimental unravelling of the molecular basis of these nucleation processes (and indeed also of more recently alternative molecular pathways 2,3,8,10,11 ) faces a fundamental challenge, namely that nucleation events are rare and stochastic in time and space. To an extent, localization of homogeneous events by, e.g, use of liquid-liquid interfaces 9 and droplets [12][13][14] has been used to overcome the spatial challenge, enabling time-resolved monitoring of structure and composition by X-ray absorption, 9,15,16 Raman 14,17 and UV/Vis spectroscopy, 17,18 SAXS 18,19 and XRD/WAXS. 13,18 However, localization is associated with confinement in small volumes, and is often introducing some degree of heterogeneity, which influences observable nucleation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…To an extent, localization of homogeneous events by, e.g, use of liquid-liquid interfaces 9 and droplets [12][13][14] has been used to overcome the spatial challenge, enabling time-resolved monitoring of structure and composition by X-ray absorption, 9,15,16 Raman 14,17 and UV/Vis spectroscopy, 17,18 SAXS 18,19 and XRD/WAXS. 13,18 However, localization is associated with confinement in small volumes, and is often introducing some degree of heterogeneity, which influences observable nucleation behavior. Indeed, for heterogeneous nucleation, methods such as atomic force microscopy (AFM), scanning electron microscopy (SEM), photoelectron emission microscopy (PEEM) and scanning tunneling microscopy (STM) have been extensively used to image nucleation and crystal growth events.…”
Section: Introductionmentioning
confidence: 99%